Electoral Institutions and Intraparty Cohesion - Matakos, Konstantinos; Savolainen, Riikka; Troumpounis, Orestis; Tukiainen, Janne; Xefteris, Dimitrios (The University of Chicago Press, 2025)
By utilizing unique data capturing candidates’ ideological positions in Finnish municipal elections and leveraging exogenous changes in council size at different population thresholds as a proxy for electoral rule disproportionality and the expected advantage to the election winner, we identify a positive effect of council size on party cohesion. We propose the following mechanism: if a more diverse set of candidates is electorally appealing but less efficient in serving policy-related goals, parties face weaker incentives to maintain cohesion in institutional settings, such as smaller councils, which reward higher vote shares more generously.